2013
DOI: 10.1111/j.1464-410x.2012.11562.x
|View full text |Cite
|
Sign up to set email alerts
|

International online survey: female ejaculation has a positive impact on women's and their partners' sexual lives

Abstract: What's known on the subject? and What does the study add?• Genital secretions during female orgasm (female ejaculation) have been a matter of controversy for centuries. Scientific work on this essential part of female sexual function has been able to differentiate between female ejaculation, urinary incontinence and vaginal transudate. According to earlier studies, less than 50% of women actually do ejaculate during sexual stimulation. Few affected women discuss female ejaculation with their physician -partly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 41 publications
0
29
0
3
Order By: Relevance
“…Immunohistochemical studies of periurethral female prostatic tissue have reported positive staining for prostate-specific antigen, prostate-specific alkaline phosphatase, and androgen receptor, consistent with female prostatic tissue. Perineal ultrasound and biochemical studies of female ejaculate in those women who have noted small volumes of fluid expulsion during orgasm have confirmed that the ejaculated fluid is rich in prostate-specific antigen and poor in creatinine and therefore biochemically similar to male ejaculate 7, 8. This is to be distinguished from large-volume “squirters” during orgasm, which is biochemically shown to be more consistent with urine 7, 8…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Immunohistochemical studies of periurethral female prostatic tissue have reported positive staining for prostate-specific antigen, prostate-specific alkaline phosphatase, and androgen receptor, consistent with female prostatic tissue. Perineal ultrasound and biochemical studies of female ejaculate in those women who have noted small volumes of fluid expulsion during orgasm have confirmed that the ejaculated fluid is rich in prostate-specific antigen and poor in creatinine and therefore biochemically similar to male ejaculate 7, 8. This is to be distinguished from large-volume “squirters” during orgasm, which is biochemically shown to be more consistent with urine 7, 8…”
Section: Introductionmentioning
confidence: 86%
“…Perineal ultrasound and biochemical studies of female ejaculate in those women who have noted small volumes of fluid expulsion during orgasm have confirmed that the ejaculated fluid is rich in prostate-specific antigen and poor in creatinine and therefore biochemically similar to male ejaculate 7, 8. This is to be distinguished from large-volume “squirters” during orgasm, which is biochemically shown to be more consistent with urine 7, 8Figure 2Panels A and B show the anterior and longitudinal aspects, respectively, of J.W.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Les ré ponses concernant l'origine du liquide sont trè s varié es et peu de femmes connaissent la nature du fluide. Prè s de 80 % des femmes interrogé es confessent que leur vie sexuelle a é té amé lioré e aprè s les premiè res é missions fontaines, alors que prè s de 10 % y voit plutôt un problè me ou une pathologie [32].…”
Section: Pré Valence Et Vé Cu Psychologique Des Femmes Fontainesunclassified
“…Dans l'é tude de Wimpissinger et al, les femmes fontaines rapportent que 90 % de leurs partenaires ont une attitude plutô t positive concernant ce phé nomè ne (avec bien sû r un biais de recrutement), 4,4 % ne sont pas au courant, 5 % sont indiffé rents et seul 0,6 % ont une vision plutô t né gative du phé nomè ne [32]. Il n'existe aucune é tude publié e s'inté ressant directement aux hommes concernant leur vé cu ou leur ressenti.…”
Section: Le Point De Vue Du Partenaireunclassified